2019
DOI: 10.4136/ambi-agua.2374
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of public squares to the reduction of urban flooding risk

Abstract: Urbanization is directly linked to the process of impermeabilization of the soil in urban areas that contributes to the emergence of flood risks. The purpose of this study was to determine the hydrodynamic properties of the public squares in a flood-prone Brazilian city and determine to what extent they could contribute to the reduction of flooding. The Beerkan method was used to determine the hydrodynamic properties of the soil in nine squares located at critical flooding points in the city of Recife. This me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The Ks values estimated by the BEST Intercept were also higher than the values of Ks estimated by BEST Slope for Sand soil. These results for Loamy Sand and Sandy Loam are in accordance with several studies in the literature (Souza et al, 2008;Di Prima et al, 2017;Sousa et al, 2019;Lassabatère et al, 2019). The Sorptivity values estimated by BEST slope and intercept were similar, with BEST slope values slightly higher.…”
Section: Scale Parameterssupporting
confidence: 91%
“…The Ks values estimated by the BEST Intercept were also higher than the values of Ks estimated by BEST Slope for Sand soil. These results for Loamy Sand and Sandy Loam are in accordance with several studies in the literature (Souza et al, 2008;Di Prima et al, 2017;Sousa et al, 2019;Lassabatère et al, 2019). The Sorptivity values estimated by BEST slope and intercept were similar, with BEST slope values slightly higher.…”
Section: Scale Parameterssupporting
confidence: 91%
“…It was demonstrated that the BEST-intercept which contains the modifications proposed by [8] presented better results than the BEST method which was originally proposed by [10]. According to [11], the K s values estimated by BESTintercept and BEST-slope are different. Regarding Sandy Loam and Loamy Sand soils, BEST-intercept estimates were higher than BEST-Slope's.…”
Section: Introductionmentioning
confidence: 98%